Public Revenue and Public Expenditure: Evidence from Sri Lanka - Anojan, Vickneswaran; Kokilan, Litharsini (Universitas Syiah Kuala, 2023)
Objective The objective of this study is to analyze the impact of public revenue on the public expenditure of Sri Lanka between 1990 and 2020.Methodology This study utilizes quantitative and secondary data from central bank publications, making the data more reliable. Tax revenue, non-tax revenue, and total revenue are independent variables, while public expenditure is the dependent variable. Descriptive and regression analyses were performed using SPSS software.Results Tax revenue is a significant contributor to Sri Lanka's total revenue, while non-tax revenue makes up a smaller portion. Additionally, the study reveals that Sri Lanka's total revenue is enough to cover nearly two-thirds of its total expenditure, with three-quarters of the country's expenses being for recurrent activities. Furthermore, the statistical analyses reveal that tax revenue has a significant impact on both current and capital expenditure in Sri Lanka, while non-tax revenue does not.Research Limitations/Implications It is also observable that many non-tax revenue-generating activities in Sri Lanka have been generating significant losses for a prolonged period. As a result, policymakers must consider discontinuing such long-term loss-making non-tax revenue activities to promote the country's economy by increasing tax revenue and gross domestic production.Novelty/Originality This study empirically deals with public revenue and expenditure with the consideration of more than thirty years of period in the Sri Lankan context.